Prenatal acetaminophen exposure and risk of wheeze at age 5 years in an urban low-income cohort. Issue 2 (22nd October 2009) - Perzanowski, Matthew S; Miller, Rachel L; Tang, Deliang; Ali, David; Garfinkel, Robin S; Chew, Ginger L; Goldstein, Inge F; Perera, Frederica P; Barr, R Graham
Abstract : Background: Acetaminophen has been associated with asthma and is in part metabolised via the glutathione pathway. Inner-city minority children have high asthma morbidity and a relatively high frequency of a minor allele variant in the glutathione S transferase Pi gene (GSTP1). We hypothesised that prenatal acetaminophen exposure would predict wheeze at age 5 years in an inner-city minority cohort and examined whether this association was modified by common polymorphisms in genes related to the glutathione pathway. Methods: An ongoing population-based birth cohort study of Dominican Republic and African-American children in New York prospectively assessed the use of analgesics during pregnancy and current wheeze at age 5 years in 301 children. Genotyping was conducted for GST polymorphisms. Binomial regression was used to adjust for potential confounders including postnatal acetaminophen use. Results: 34% of mothers reported acetaminophen use during pregnancy and 27% of children had current wheeze at 5 years. Prenatal exposure to acetaminophen predicted current wheeze (multivariate relative risk 1.71; 95% CI 1.20 to 2.42; p=0.003), and the risk increased monotonically with increasing number of days of prenatal acetaminophen exposure (p trend <0.001). 68% of children had at least one copy of the GSTP1 minor allele (Val). The risk of wheeze was modified by GSTP1 (additive interaction p=0.009) and was observed only among children with the GSTP1 minor allele. Conclusions: Prenatal exposure to acetaminophen predicted wheeze at age 5 years in an inner-city minority cohort. The risk was modified by a functional polymorphism in GSTP1, suggesting a mechanism involving the glutathione pathway.